2016
DOI: 10.1002/mgg3.230
|View full text |Cite
|
Sign up to set email alerts
|

ADGRL 3 ( LPHN 3) variants are associated with a refined phenotype of ADHD in the MTA study

Abstract: Background ADHD is the most common neuropsychiatric condition affecting individuals of all ages. Long‐term outcomes of affected individuals and association with severe comorbidities as SUD or conduct disorders are the main concern. Genetic associations have been extensively described. Multiple studies show that intronic variants harbored in the ADGRL3 (LPHN3) gene are associated with ADHD, especially associated with poor outcomes.MethodsIn this study, we evaluated this association in the Multimodal Treatment S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Kim et al recently identified that Glis3 could regulate neurogenin-3 expression in pancreatic β-cells [45]. Acosta et al applied experiment and confirmed that Adgrl3 variants are associated with a refined phenotype of attention-deficit/hyperactivity disorder(ADHD) in the MTA study [46]. An ultraconserved brain-specific enhancer in ADGRL3 were reported withADHD susceptibility [47].…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al recently identified that Glis3 could regulate neurogenin-3 expression in pancreatic β-cells [45]. Acosta et al applied experiment and confirmed that Adgrl3 variants are associated with a refined phenotype of attention-deficit/hyperactivity disorder(ADHD) in the MTA study [46]. An ultraconserved brain-specific enhancer in ADGRL3 were reported withADHD susceptibility [47].…”
Section: Resultsmentioning
confidence: 99%
“…Allele calling was made by end-point fluorescent signal analysis using the ABI’s SDS2.3 software. In addition, we had previously collected exome genotype data from the MTA sample 26 using the Infinium ® HumanExome-12 v1.2 BeadChip kit (Illumina), which covers putative functional exonic variants selected from over 12,000 individual exome and whole-genome sequences. Processed and raw intensity signals for the array data can be accessed at GEO (GSE112652).…”
Section: Methodsmentioning
confidence: 99%
“…Using genome-wide data from extended multigenerational families, we found evidence of linkage of ADHD to markers in chromosomes 4q13.2, 5q33.3, 8q11.23, 11q22, and 17p11 25 , and co-segregation of ADHD and disruptive behaviors with loci at 2p21-22.3, 4q13.2, 5p13.1-p13.3, 8q24, 8q15, 11q22, 12p11.23-13.3, and 14q21.1-22.2 8 . Fine mapping of the 4q13.2 region identified variants in the adhesion G-protein-coupled receptor L3 gene (ADGRL3 , also known as latrophilin 3 or LPHN3) that predispose to ADHD 22,24,2630 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors are strongly implicated in the aetiology of ADHD, CD, ODD, and SUD [6,10,11,12]. In particular, common single nucleotide polymorphisms (SNPs) harboured in the Adhesion G-protein-coupled receptor L3 ( ADGRL3 , also known as Latrophilin 3 or LPHN3 ; markers rs2345039, rs6551665, and rs1947274), the Synaptosomal-associated protein of molecular weight 25 kDa ( SNAP25 ), the Fibroblast growth factor 1 ( FGF1 ), the Solute carrier family 6 (neurotransmitter transporter, noradrenalin) member 2 ( SLC6A2 ), and the Dopamine receptor D4 ( DRD4 ) genes predispose one to ADHD [6,13], as confirmed by worldwide replications [2,3,6,14,15,16,17,18,19,20,21].…”
Section: Introductionmentioning
confidence: 98%